ESTABLISHMENT OF THE BUKHARA MILITARY COMMISSION IN THE BUKHARA PEOPLE’S SOVIET REPUBLIC - Zokirov Bobir Chorievich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
After the amir’s power was overthrown due to the attack of the Red Army on Bukhara, on October 6, 1920, the First Congress of All-Bukhara People’s Representatives began its work. The first Convention decides to declare Bukhara People’s Soviet Republic (BPSR). The main tasks of the Bolsheviks were to send the treasury of the Emirate to the Center, to increase the number of the Red Army, to confiscate the property of large lairds who worked during the time of the Emir, and to punish them, and to conclude a military-political agreement between the RSFSR